Experimental performance of evaporative cooling pad systems in greenhouses in humid subtropical climates. (15th January 2015) - Xu, J.; Li, Y.; Wang, R.Z.; Liu, W.; Zhou, P.
Highlights: Experimental performance of evaporative cooling in humid climate is investigated. 5 working modes are studied in the greenhouse. Vertical and horizontal temperature and relative humidity variations are analysed. Indoor temperature can be kept in required level by proper working modes. Abstract: To solve the overheating problem caused by the solar radiation and to keep the indoor temperature and humidity at a proper level for plants or crops, cooling technologies play vital role in greenhouse industry, and among which evaporative cooling is one of the most commonly-used methods. However, the main challenge of the evaporative cooling is its suitability to local climatic and agronomic condition. In this study, the performance of evaporative cooling pads was investigated experimentally in a 2304-m 2 glass multi-span greenhouse in Shanghai in the southeast of China. Temperature and humidity distributions were measured and reported for different working modes, including the use of evaporative cooling alone and the use of evaporative cooling with shading or ventilation. These experiments were conducted in humid subtropical climates where were considered unfavourable for evaporative cooling pad systems. Quantified analyses from the energy perspective are also made based on the experimental results and the evaporative cooling fan–pad system is demonstrated to be an effective option for greenhouse cooling even in the humid climate. Suggestions and possible solutions for further improving the performance of the system are proposed. The results of this work will be useful for the optimisation of the energy management of greenhouses in humid climates and for the validation of the mathematical model in future work.